2022
DOI: 10.1186/s40798-021-00399-3
|View full text |Cite
|
Sign up to set email alerts
|

The Reliability of Transcranial Magnetic Stimulation-Derived Corticomotor Inhibition as a Brain Health Evaluation Tool in Soccer Players

Abstract: Background The suitability of corticomotor inhibition and corticospinal excitability to measure brain health outcomes and recovery of sport-related head impact (concussion and subconcussion) depends on good inter-day reliability, which is evaluated in this study. Transcranial magnetic stimulation (TMS) reliability in soccer players is assessed by comparing soccer players, for whom reliability on this measure may be reduced due to exposure to head impacts, to generally active individuals not eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 44 publications
2
5
0
Order By: Relevance
“…The duration of the silent period can provide information about the inhibition at the cortical or spinal level (Inghilleri et al, 1993). Reliability of LS-elicited SP were moderate and good, which were slightly higher than the TMS-elicited SP reported by Di Virgilio et al (2022). Furthermore, CV were similar to those reported previous (CV = 7-15%) (O'Leary et al, 2015;Leung et al, 2018;Di Virgilio et al, 2022).…”
Section: Silent Period Reliabilitysupporting
confidence: 84%
“…The duration of the silent period can provide information about the inhibition at the cortical or spinal level (Inghilleri et al, 1993). Reliability of LS-elicited SP were moderate and good, which were slightly higher than the TMS-elicited SP reported by Di Virgilio et al (2022). Furthermore, CV were similar to those reported previous (CV = 7-15%) (O'Leary et al, 2015;Leung et al, 2018;Di Virgilio et al, 2022).…”
Section: Silent Period Reliabilitysupporting
confidence: 84%
“…Cortical silent period is a cortical excitability measure that reflects the duration of the period of suppression in electromyographic activity that typically follows a single TMS pulse delivered to the primary motor cortex while a mild voluntary contraction of the corresponding muscle of interest is being performed ( 49 ). It has good test-retest reliability under different conditions and methodological implementations ( 50 , 51 ), making it a potentially useful marker of disease and/or treatment response for this clinical population. There is evidence that CSP reflects intracortical GABAergic activity, more specifically GABA B receptor activity ( 52 , 53 ), and our results are thus aligned with existing evidence that GABA B receptor function may be impaired in OCD.…”
Section: Discussionmentioning
confidence: 99%
“…Quadriceps active motor threshold (aMT) was determined by increasing stimulator output in 5% increments, starting from 10%, until a discernible MEP was visible during sustained contraction at an intensity equivalent to 20% of participant MVC achieved during that testing session (Wilson et al 1995 ); contraction intensity was maintained by the participant tracing their contraction force to a template visible on a computer monitor directly in front of them. Subsequent stimulations were delivered at 130% of aMT, this protocol has previously demonstrated a high level of reliability in our laboratories (Di Virgilio et al 2022 ). A study by Temesi et al ( 2014 ) found no differences between VL, RF, and vastus medialis for aMT or resting MT stimulus–response curves; suggesting that one muscle can be considered representative of all three.…”
Section: Methodsmentioning
confidence: 99%